Provenance of uranium particulate contained within Fukushima Daiichi Nuclear Power Plant Unit 1 ejecta material - Peter G. Martin (Nature Portfolio, 2019)
The larger particulates from reactor Unit 1 of the Fukushima Daiichi Nuclear Power Plant have received sparse attention compared to the Unit 2 particulate. Here the authors perform the higher-resolution and 3-dimentional analysis of several high-density micron-scale fragments, from within a larger Unit 1-derived representative ejecta particle.